Digital signatures : the impact of digitization on popular music sound - Brøvig-Hanssen, Ragnhild; Danielsen, Anne (The MIT Press, 2016)
How sonically distinctive digital "signatures"--Including reverb, glitches, and autotuning -- affect the aesthetics of popular music, analyzed in works by Prince, Lady Gaga, and others